Serology reveals comparable patterns in the transmission intensities of Plasmodium falciparum and Plasmodium vivax in Langkat district, North Sumatera Province, Indonesia - Inke Nadia Diniyanti, Lubis; Irbah Rea Alvieda, Nainggolan; Meliani, Meliani; Beby Syofiani, Hasibuan; Kumuthamalar, Sangaran; Luqman, Samsudin; Sriwipa, Chuangchaiya; Paul Cliff Simon, Divis; Ranti, Permatasari; Zulkarnain Md, Idris (Frontiers Media S.A., 2025)
Introduction: The incidence of malaria in Indonesia has declined significantly over the last few decades. Thus, a demand for more sensitive techniques to describe low levels of transmission in the country is important. This study was conducted to evaluate antibody response to Plasmodium falciparum and Plasmodium vivax in an area nearing elimination in North Sumatera Province, Indonesia.